Thickness dependence of the superconducting properties of γ- Mo2N thin films on Si (001) grown by DC sputtering at room temperature - Haberkorn, Nestor Fabian (2018)
We study the crystalline structure and superconducting properties of γ-Mo2N thin films grown by reactive DC sputtering on AlN buffered Si (001) substrates. The films were grown at room temperature. The microstructure of the films, which was studied by X-ray diffraction and transmission electron microscopy, shows a single-phase with nanometric grains textured along the (200) direction. The films exhibit highly uniform thickness in areas larger than 20 × 20 μm2. The superconducting critical temperature Tc is suppressed from 6.6 K to ≈ 3.0 K when the thickness decreases from 40 nm to 5 nm. The residual-resistivity ratio is slightly smaller than 1 for all the films, which indicates very short electronic mean free path. The films are in the superconducting dirty limit with upper critical field Hc2 (0) ≈ 12 T for films with thickness of 40 nm, and 9 T for films with thickness of 10 nm. In addition, from the critical current densities Jc in the vortex-free state, we estimate a penetration depth λ(0) ≈ (800 ± 50) nm and a thermodynamic critical field Hc (0) = (500 ± 80 Oe).